2021
DOI: 10.36076/ppj.2021/24/e349
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebroplasty Versus Kyphoplasty for Thoracolumbar Osteoporotic Vertebral Compression Fractures in Patients with Distant Lumbosacral Pain

Abstract: Background: In clinical practice, we have found that the pain caused by thoracolumbar osteoporotic vertebral compression fracture (OVCF) is sometimes not limited to the level of the fractured vertebrae but instead occurs in areas far away from the injured vertebrae, such as the lower back, area surrounding the iliac crest, or buttocks, and this type of pain is known as distant lumbosacral pain. The pathogenesis of pain in distant regions caused by thoracolumbar OVCF remains unclear. Objectives: To compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…There were few studies reported that percutaneous kyphoplasty could alleviate the DLP. [3][4][5][6] The results of this study showed signi cant improvements in the Cobb angle, anterior vertebral heights, VAS and CMODI after surgery. These outcomes can be attributed to the ability of PVP to restore vertebral height, eliminate micro-motion within the fractured vertebra, and alleviate the mechanical load exerted on the facet joints.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There were few studies reported that percutaneous kyphoplasty could alleviate the DLP. [3][4][5][6] The results of this study showed signi cant improvements in the Cobb angle, anterior vertebral heights, VAS and CMODI after surgery. These outcomes can be attributed to the ability of PVP to restore vertebral height, eliminate micro-motion within the fractured vertebra, and alleviate the mechanical load exerted on the facet joints.…”
Section: Discussionmentioning
confidence: 98%
“…[3 , 6] It is commonly observed that lumbosacral pain in older patients is primarily attributed to degenerative changes in the lumbosacral region, [11][12][13] whereas the association between thoracolumbar OVCF and lumbosacral pain is less frequently documented. [6 , 14] Li et al [5] found that 33.9% of patients suffering from thoracolumbar OVCF experienced pain solely in the distant lumbosacral region, rather than in the immediate vicinity of the fractured vertebra. Given the prevalence of lumbar degenerative changes in the elderly population, these OVCF patients are susceptible to being misdiagnosed with lumbar degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Early PVPs or PKPs without an initial trial of conservative therapy may be considered as overtreatment. On the contrary, delayed procedures may not be as effective, not only in reducing a potentially wedged vertebra, but also in dealing with residual pain [ 13 ]. We are inclined more towards early VPs because we consider fracture reduction to be sufficiently achievable only in acute fractures.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the relationship between timing of BKP and clinical outcomes, a latest systematic review and meta-analysis of 13 studies concluded that early BKP intervention was associated with similar or better outcomes in terms of pain relief, functional improvement, restoration of vertebral height, and correction of kyphosis deformity when compared to delayed BKP intervention [ 45 ]. A meta-analysis showed no significant difference in cement leak rates between early and late BKP (OR, 1.60; 95% CI, 0.97–2.64; p = 0.07), while delayed BKP was associated with a higher risk of adjacent vertebral fracture than early BKP (OR, 0.31; 95% CI, 0.…”
Section: Are Orthotics Useful For Ovf?mentioning
confidence: 99%